2015
DOI: 10.3989/rdtp.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

(Des)naturalización y elección: emergencias en la parentalidad y el parentesco de lesbianas, gays, bisexuales y transexuales

Abstract: is still based on «coupling» and the desire to maintain genetic ties in order to legitimise filiation. As such, LGBT families are engaged in a creative transformation of traditional kinship, broadening and redefining the concept to incorporate same-sex and heterosexual families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 2 publications
1
5
0
12
Order By: Relevance
“…Like in the current study, early studies in Spain showed that most LGB parents have had children in previous heterosexual relationships (González & López, 2009). However, a more recent study in Spain has shown that the majority of LGB families are now planned through adoption and donor insemination (Galán, Barbero, & Martín-Chiappe, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Like in the current study, early studies in Spain showed that most LGB parents have had children in previous heterosexual relationships (González & López, 2009). However, a more recent study in Spain has shown that the majority of LGB families are now planned through adoption and donor insemination (Galán, Barbero, & Martín-Chiappe, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…En efecto, las personas pueden recurrir a los donantes 29 Imax, 2006. 30 Pichardo et al (2015), p. 188. 31 Herrera et al, 2018a.…”
Section: Metodologíaunclassified
“…The possibility of private co-parenthood arrangements is not supported by law and, in any case, for women it is not a very attractive option, as they see no advantages in it, only problems. With the other possibilities ruled out as unfeasible, surrogacy in a foreign country is the only option that is seen as viable, although it is seldom viewed as the option they would have chosen under different circumstances ( Pichardo et al, 2015; 193 ). Surrogacy raises ethical concerns and is greatly resisted by public opinion, and it is also an extremely costly procedure that is opaque and complicated for the prospective parents ( Smietana, 2011 ).…”
Section: Reflecting On the Asymmetry Between Men And Women In Same-sementioning
confidence: 99%